(untitled) (Journal of Parents and Teachers, 2014)
Educational quality implies, among many other aspects, a continuous and unbiased evaluation in which the alumni have to participate. The article offers ideas to recover the figure of the same, such as celebrate a day in his honor or make a newsletter.